TINJAUAN HUKUM ISLAM DAN KHI TERHADAP PENGULANGAN IJAB QABUL (STUDI KASUS DI KUA KECAMATAN PLOSO KABUPATEN JOMBANG) - Walidaini, Ahmad Birul; Fitri, Abdul Basit Misbachul; Aminah, Siti (Jurnal Studi Multidisiplin Qomaruna, 2024)
Marriage is a sacred bond between a man and a woman, based on mutual consent and a valid vow, known as ijab and qabul. Ijab is the statement from the guardian, while qabul is the agreement from the groom, witnessed by two witnesses. This study uses a qualitative approach to understand the phenomenon of repeating ijab qabul in Ploso Subdistrict, Jombang Regency. Data collection techniques involve surveys and interviews with both prospective brides and grooms, their families, and the local Head of the Office of Religious Affairs (KUA). The results of the study show that the repetition of ijab qabul in Ploso is carried out according to KUA procedures, meeting the requirements of Islamic law and positive law. This repetition, although unique, does not invalidate the first ijab qabul but is a form of caution and elimination of doubt. This study provides scientific insights into the phenomenon of repeating ijab qabul, which has not been previously researched, and answers legal questions regarding the validity of such repetition